Moral decisions in video games and players’ intergroup attitudes - Koek, Dominic Wei Jie (2022)
This study examined how players’ in-game decisions on the six moral foundation domains when interacting with NPCs influenced attitudes toward immigrants. A 3 (citizen vs. mixed citizen and foreign vs. foreign NPCs) by 2 (moral vs. neutral) experiment was conducted (N = 300). Participants in the mixed NPCs condition experienced significantly lower post-game attitudes toward immigrants. Participants who violated care/harm in-game experienced higher levels of guilt, but this had no impact on attitudes regarding immigrants.